PENGARUH PENERAPAN VIDEO ANIMASI TERHADAP HASIL BELAJAR BIOLOGI SISWA KELAS VIII DI SMP NEGERI 2 TINONDO - Tendrita, Miswandi; Alonemarera, A; Gunawan Putri, Sartika; Saparuddin; Erfina (Jurnal Biogenerasi, 2024)
The biology learning scores of class VIII students at SMP Negeri 2 Tinondo have not achieved the expected results. This is thought to be due to a lack of involvement in learning media, especially audio-visual media. Meanwhile, biology often involves complex and abstract concepts. Audio visual media such as animated videos can help students understand these concepts more clearly and concretely. Therefore, this research aims to determine the effect of implementing animated videos on the biology learning outcomes of class VIII students at SMP Negeri 2 Tinondo. This research was a pre-experiment type involving one experimental class with a total of 17 students. Class determination uses totally sampling technique. Through the test technique, pre-test and post-test learning results test sheets are used, each consisting of 10 multiple choice questions and 3 essay questions. Data were analyzed descriptively and inferentially (paired-sample t-test). The research results showed that the average student pre-test score was 39.18 (poor category) and student post-test score was 77.65 (good category). From the results of hypothesis testing, a sig value was obtained. 0.000 < 0.05. Thus, it can be concluded that there is an influence of the application of animated videos on the biology learning outcomes of class VIII students at SMP Negeri 2 Tinondo.